Formal, Non-formal, and Informal Islamic Education Institutions and Islamic Education Figures in Indonesia - Andi Anis Magfiroh; Muflih Naufal Irfan; Rahmat Rahmat; Besse Ruhaya (Journal of Indonesian Islamic Studies, 2023)
The purpose of this article is to describe formal, non-formal and informal Islamic educational institutions and their figures in Indonesia. The method used in this research is library research. The results of the research are: 1) Formal education iseducation directly supervised by the governmentÂnational constitution in accordance with laws and other juridical laws that regulate levels, curricula, educational staff and so on. Educational institutionsÂit's thereIslamic madrasas and colleges; 2) Non-formal education is an educational pathway that is held in the form of book recitation, taklim assemblies, al-Qur'an education, diniyah takmiliyah which consists of several levels, and other similar forms; 3) Informal education is a path of family and environmental education where learning activities are carried out spontaneously, do not require a learning design and are carried out at any time. InstitutionÂeducation is family and community environment; and 4) Islamic education figures in Indonesia are Ki Hajar Dewantara whose birthday is enshrined as national education day, Ahmad Dahlan who is known as the founder of the Muhammadiyah organization and KH. Hasyim Asy'ari who is known as the founder of Nahdhatul Ulama with an educational concept that aims to form a highly ethical society.